Estructura de la comunicación empresarial - Enrique Jiménez, Ana María; Morales Serrano, Francisca (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2009)
This article tries to throw light on the communication management structure taking as a reference the models from secondary sources and an empirical research of qualitative character. From a sample of 22 companies (11 of consumption and 11 of services) it is studied the denomination provided to the person in charge of communication and to the department that represents, who is the person of the company she or he reports with, how they define the communication model that they implement and what types of communication are coordinated and managed by the figure in charge of the communication in the company